Online Learning Activities (Case Study on Students of the Open University Economic Education Study Program) - Sri Sumiyati (Universitas Muhammadiyah Enrekang, 2023)
This research is motivated by the importance of online learning activities in improving student learning outcomes. This study uses a qualitative research method with a case study approach and is descriptive in nature. The place and time of this research is the Study Program of Economic Education, Faculty of Teacher Training and Education, Open University, Even Semester, Academic Year 2022/2023 Course in Geography and Environmental Conservation. Data collection techniques namely observation, interviews and documentation. Data analysis techniques carried out were data reduction, data presentation, and verification. Implementation of case studies includes planning, case descriptions, classifying types of problems, describing problems, collecting data, data processing, synthesis and interpretation, evaluation and follow-up. The results of this study indicate that 1) Students who have high scores are those who always access initiation materials one through eight, by working on the first assignment, second assignment and third assignment, 2) Students who have low scores are students who do not access any of the first initiation materials up to eight, but still working on the first task, second task or third task, and 3) Obstacles faced why students do not access initiation materials are caused by several things, namely busy work, sometimes network constraints in their area are not good, so that during initiation students experience delays upload assignments or answer the discussion of each initiation.